NDF (Neutral Detergent Fiber) and ADF (Acid Detergent Fiber) In Vitro Digestibility of Fermented Complete Feed with Lemongrass Oil Distillation Waste - Hartati, Lilis; Septian, Mohamad Haris; Afsari, Restiana Nur (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aims to evaluate the potential of fermented lemongrass distillation waste as a complete feed for ruminant livestock by assessing in vitro digestibility of NDF and ADF. The study was designed using a Completely Randomized Design (CRD) with five treatments and four replications, including: P0 (60% Elephant Grass + 0% Lemongrass Distillation Waste + 40% Concentrate), P1 (40% Elephant Grass + 20% Lemongrass Distillation Waste + 40% Concentrate), P2 (30% Elephant Grass + 30% Lemongrass Distillation Waste + 40% Concentrate), P3 (20% Elephant Grass + 40% Lemongrass Distillation Waste + 40% Concentrate), and P4 (0% Elephant Grass + 60% Lemongrass Distillation Waste + 40% Concentrate). The observed parameters were in vitro NDF digestibility and ADF digestibility. Data were analyzed using analysis of variance (ANOVA). The differences in the use of fermented lemongrass distillation waste in complete feed did not affect (P>0.05) the in vitro digestibility of NDF and ADF, with an average NDF digestibility of 69.24 ± 10.42% and an average ADF digestibility of 36.97 ± 7.18%. The results of this study conclude that lemongrass distillation waste can be utilized as an alternative fiber source in formulating complete feed for small ruminant livestock.